2022
DOI: 10.1021/acsomega.2c05064
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of ZnS Monolayer Adsorption Behavior for CO and HF Gas Molecules

Abstract: Adsorption of carbon monoxide (CO) and hydrogen fluoride (HF) gas molecules on a ZnS monolayer with weak van der Waals interactions is studied using the DFT + U method. From our calculation, the ZnS monolayer shows chemisorption with CO (E ads = −0.96 eV) and HF (E ads = −0.86 eV) gas molecules. Bader charge analysis shows that charge transfer is independent of the binding environment. A higher energy barrier for CO when migrating from one optimal site to another suggests that clustering may be avoided by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…It is calculated that the charge transfer between the HF and CuCl monolayer is −0.04 e , which is a bit greater than that in previous studies, 35 and similarly we observed a high charge transfer of 0.03 e for the CO/CuCl ML as compared to that in previous studies. 30,32–35 It is observed from the calculations that the charge transfer is independent of the Hubbard parameter, i.e. , the local binding environments, and only relies upon the properties of the adsorbed gas and the nature of the monolayer, which is compatible with the findings of previous studies.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…It is calculated that the charge transfer between the HF and CuCl monolayer is −0.04 e , which is a bit greater than that in previous studies, 35 and similarly we observed a high charge transfer of 0.03 e for the CO/CuCl ML as compared to that in previous studies. 30,32–35 It is observed from the calculations that the charge transfer is independent of the Hubbard parameter, i.e. , the local binding environments, and only relies upon the properties of the adsorbed gas and the nature of the monolayer, which is compatible with the findings of previous studies.…”
Section: Resultssupporting
confidence: 87%
“…It is observed that at RT, the value of the recovery time of CO on CuCl ML is 1.69 × 10 18 s, while HF molecules show a more rapid recovery time of 1.09 × 10 −7 s, which is much less than that found in previous studies on HF (4.68 min). 34 This indicates that we can achieve active sensing with a fast recovery time for HF at RT (300 K). 56,57 Further calculations are carried out to determine the changes with various temperatures.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations